Effect of inventory plot patterns in the floristic analysis of tropical woodland and dense forest. - Houeto, Georges; Glèlè Kakaï, Romain Lucas; SALAKO, Kolawolé Valère; Fandohan, Adandé Belarmain; ASSOGBADJO, ACHILLE EPHREM; SINSIN, Brice; PALM, Rodolphe (My University, 2013)
This study was set up to examine the effect of plot patterns on the accuracy of phytosociological characterization of tropical vegetation. Fifteen and twenty square plots of 1 ha were demarcated, respectively, in woodland and dense forest in Bénin. Each 1 ha plot was divided into 100 quadrats of one 100 m2. Species of trees in each quadrat were identified and recorded. The cost in terms of time required to record tree species in each 1 ha plot and five random quadrats in a 1 ha plot were also recorded to compute the mean inventory effort for a team of three foresters. From the 100 quadrats in a 1 ha plot, fourteen independent subplots of square and rectangular plots with different sizes were considered by grouping together adjacent quadrats of 100 m2. Eigenanalysis was carried out to compare the subplots. Moreover, the relationship between the relative loss of accuracy (RLA) and the size of subplots was modelled. Plot size highly influenced the RLA (P < 0.05). Findings indicated that the square plots of 1500 and 1000 m2 with an inventory effort of 0.35 and 0.20 man-days per subplot, respectively in tropical dense forests and woodlands appeared to be the most efficient in the phytosociological characterization of woody vegetation.
Keywords: Benin; efficiency; eigenanalysis; floristic analysis; inventory plot; vegetation